The Role of Case Hardening in the Preservation of the Cavates and Petroglyphs of Bandelier. (28th March 2017) - Porter, Douglas; Broxton, David; Bass, Angelyn; Neher, Deborah A.; Weicht, Thomas R.; Longmire, Patrick; Spilde, Michael; Domingue, Rebecca
ABSTRACT: Bandelier National Monument (BNM) was created to protect an extraordinary inventory of archaeological resources carved in the Tshirege Member of the Bandelier Tuff. These include more than one thousand excavated chambers, called cavates, used for dwelling, storage, and textile production. The glass-rich tuffs at the base of the Tshirege Member are poorly consolidated and susceptible to erosion by wind, rain, and mechanical abrasion, with resultant loss of cultural material. However, rock surfaces develop protective weathering rinds that are resistant to erosion. Using optical microscopy, SEM-EDS, XRD, and electron microprobe analysis, we determined that this rind consists of clay and silt sediments colonized by lichens and other surface biota, accompanied by the precipitation of secondary minerals in the near-surface pore space. Scoping experiments focused on glass-organic acid interactions indicate that oxalic acid excreted by microbial crust constituents catalyzes biogeochemical reactions that lead to the preferential dissolution of Si, Al, and Fe components of the volcanic glass; these cations become available for precipitation of opal, and smectite and sepiolite clays. Enzyme assays that quantify biological activity at outcrop surfaces indicate that microbial populations initially thrive as they derive nutrients from the dissolution reactions of the glass, but activity starts to decline as precipitation of secondary minerals limits access to new sources of nutrients, so that alteration processes are self-limiting. As case hardening progresses, imbibition rates at the surface decrease, and the erosion resistance of the altered surfaces is substantially improved. This article presents summary results of research conducted over a period of five years to characterize the roles of lichens and other microflora in rind formation, and the resulting contributions to tuff stability. The interaction of lichens and other microflora with rock surfaces in archaeological sites and monuments is usually explored in terms of biodeterioration and consequent damage. However, this study shows that, under some circumstances, lichens and microflora provide a level of erosion protection to relatively porous and unconsolidated rock strata that outweighs their biodeteriorative effects.